Bridging Data Management and Decision-Making: The Role of Data Warehousing in Enhancing Business Intelligence - Iranna Shirol (International Journal of Scientific Research in Science, Engineering and Technology, 2025)
In today's data-rich environment, effective decision-making hinges on the ability to transform raw data into actionable insights. This research paper empirically examines how advanced data warehousing architectures directly influence business intelligence (BI) outcomes. By integrating quantitative performance metrics with qualitative insights from case studies and expert interviews, the study evaluates the contribution of data warehousing components—such as data quality, query performance, and real-time data integration—to enhanced decision-making processes. The results reveal that strategic investment in data warehousing can significantly improve the speed and accuracy of BI, guiding organizations toward more informed and agile business strategies.
Keywords: Data Warehousing; Business Intelligence; Data Management; Decision-Making; ETL; Real-Time Analytics